Correlation of Semantic Understanding with Al-Qiraah An-Naqdiyah Learning Achievement - Nugrahawan, Ahmad Rizki; Wahidul Akbar, Doni (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
In the Arabic Education curriculum, the Qiraah Naqdiyah course is about Mafhumul Maqru. Therefore, related to understanding the meaning of reading, it cannot be separated from semantic meaning (Dalalah). This research aims to determine the correlation between understanding Dalalah and Qiraah Naqdiyah courses. This research method is a Quantitative method with a correlative study approach and uses the Pearson correlation test. The data collection techniques are through questionnaires and tests. The object of this research is PBA UHAMKA Jakarta Students. The data used are the results of the Dalalah Science and Qiraah Naqdiyah tests. This research indicates that the correlation between grades in the Dalalah and the Qiraah courses, both from class A and class B, could be more robust. The synergy between Dalalah science courses as an approach to supporting Qiraah Naqdiyyah courses needs to be improved so that the achievement of Qiraah Naqdiyyah can be optimal.